Holistic Analysis and Management of Distributed Social Systems - Sapaty, Peter Simon (Studies in Systems, Decision and Control, 2019)
This book describes the application of a high-level technology to solve problems in distributed systems that have networked structures with millions to billions of nodes. The main difference from other works is that the approach is based on holistically and simultaneously analysing these systems using a spatial pattern-matching mode, which produces solutions hundreds of times faster than usual. The latest version of the technology is described, together with implementation details and basic Spatial Grasp Language. In addition, the book highlights numerous solutions, covering graph and network problems, their use in large social, industrial, and business ecosystems, social robotics and driverless transport, and the possibility of extrapolating from known gestalt laws on distributed systems, which could potentially be applied in civil and defence contexts. The book is intended for system scientists, business and industry managers, economists, application programmers, security and defencepersonnel, as well as university students.